Análisis de la rentabilidad en el Comercial Silvana María del cantón Baba - Barboto Suñiga, Ricardo Antonio (2021)
This study was carried out in order to analyze the financial statements of the commercial "SILVANA MARÍA", a company dedicated to the commercialization of various products such as food and beverages in the Baba canton. This evaluation focuses on the decrease in profits from one period to another, which is why the inductive method was implemented, starting from generalized observations to reach a conclusion, complementing with a more detailed analysis that includes a horizontal analysis, vertical analysis and ratios. specific financial statements to verify the effectiveness of the company's purchases and sales. As a result of the study, it was determined that the quality of the inventory and the management of assets and capital directly affects the profit margin generated in the period and the liquidity capacity, which means that even when its sales increase, it will not be able to solve its obligations immediately since their costs and expenses have a greater increase in percentage terms.